The Role and Challenges of Women's Empowerment Programs in Reducing Household Poverty - Fadriyansyah Munggaran (CV. Sutan Mandiri Sejahtera, 2026)
This study aims to analyze the strategic role of women's empowerment programs in alleviating household poverty and identify various cultural and structural challenges in their implementation. Using qualitative methods with a library research approach, secondary data was collected through a review of reputable scholarly articles, textbooks, and official reports over the past ten years. The results reveal two main findings. First, economically, empowerment programs through skills training and micro-capitalization play a significant role in generating new income as a family financial safety net, which has implications for improving women's bargaining power and democratizing domestic decision-making. Second, the sustainability of these programs faces significant challenges, including cultural barriers, a dual burden resulting from a strong patriarchal culture, and structural constraints, including project-oriented program traps, financial exclusion from formal banking, and minimal post-training mentoring. This study concludes that strengthening women's capacity requires inclusive policy transformation, gender-friendly follow-on capital schemes, and sustainable business mentoring to break the chain of structural poverty.